PENYIMPANAN BAHAN MAKANAN PASTRY UNTUK MEMPERTAHANKAN MUTU PRODUK DI HOTEL GRAND CENTRAL PEKANBARU - Ranti Permata Afra; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Storage of foodstuffs is a very important thing to pay attention to because basically foodstuffs are easily damaged, especially if they are stored irregularly, in an unclean room, and not maintained properly which will affect the quality and quality of the product. Paying attention to the method of storing foodstuffs, both raw and cooked, is a priority to be carried out in accordance with existing provisions so that the product that will be produced remains in good quality. The purpose of this study was to determine how the method of storing pastry foodstuffs and the constraints in carrying out the method of storing pastry foodstuffs. The data collection method was carried out by carrying out field work practices for 4 months at Grand Central Hotel Pekanbaru, interviews, and collecting data from books and journals with qualitative data analysis techniques as a supporting factor in this study. The results of this study can be concluded that in terms of storage, the pastry kitchen at Grand Central Hotel Pekanbaru has a method of storing food ingredients in accordance with the HACCP (Hazard Analysis and Critical Control Point) system and its application is quite good based on the type of food ingredients. Keywords: Storage method, Pastry, Grand Central Hotel Pekanbaru.